Dengue Fever: Addressing Ghana’s Emerging Public Health Crisis - Felix Amekpor; Snehasish Tripathy; Ebuka Louis Anyamene; Wucharey Kwasi Daniel; Anyannor Emmanuel; Vini Mehta (National Journal of Community Medicine)
This study explores the public health concerns, challenges, and solutions surrounding dengue fever reemergence in Ghana. Several environmental factors such as open drainage system, improper waste disposal, improper storage of water influence the transmission of dengue disease in Ghana.  Ghana is also dealing with issues related to increased global commerce and tourism, inadequate sanitation such as open drainage system, improper waste disposal and inadequate mosquito control measures which could lead to increased vulnerability to dengue outbreaks. Poor healthcare infrastructure, poverty, geographical inaccessibility, a shortage of skilled healthcare workers, lack of awareness among community members, and weak vector surveillance system further exacerbate the issue. Thus, there is an urgent need for coordinated efforts among policymakers, healthcare professionals, and the general public. Increasing public awareness through co-creation approaches, strengthening laboratory diagnostics, investing in healthcare professionals training, scaling up integrated vector management activities stakeholders can mitigate the risk of severe dengue complications in Ghana.